Ten questions a sociological perspective - Charon, Joel M. 1939- (Australia Wadsworth Cengage Learning, 2013)
From the Publisher: What does it mean to be human? Are human beings free? Why is there misery in the world? Ten Questions: A Sociological Perspective examines the philosophies of the classical sociologists such as Marx, Weber, Durkheim, Mead, and Berger and looks at how the field of sociology has approached these questions over the past 150 years.
8: Does The Individual Really Make A Difference?: An Introduction To Social Change -- Concepts, themes, and key individuals -- Individual's influence on his or her own life -- Individual's influence on other individuals -- Individual versus social organization -- Social change: a sociological view -- Some implications for living -- Summary and conclusion -- Questions to consider -- References -- 9: Is Organized Religion Necessary For Society?: Tradition, Modernization, And Secularization -- Concepts, themes, and key individuals -- Defining religion -- Social functions of religion -- Is organized religion still necessary? -- Summary and conclusion -- Questions to consider -- References -- 10: Is The World Becoming One Society?: Globalization And The Creation Of A World Society -- Concepts, themes, and key individuals -- Three views of globalization -- New Technology, new communication, and new globalization -- Capitalism -- Is globalization creating a "world society"? -- Is globalization good for the world? -- Conclusion: globalization and a world society -- Questions to consider -- References -- 11: Why Study Sociology?: Understanding, Questioning, And Caring -- Concepts, themes, and key individuals -- Sociology and democracy -- Sociology is more than the study of democracy -- Summary and conclusion -- Questions to consider -- References -- Afterword: Should we generalize about people?: generalizing, categorizing, stereotyping, and the importance of social science -- Concepts, themes, and key individuals -- Categories and generalizations -- Stereotype -- Social science: a reaction to stereotypes -- Summary and conclusion -- Questions to consider -- References -- Glossary -- Bibliography-- Index.
Includes bibliographical references (p. 343-353) and index.
Keywords: Sociology; United States -- Social conditions